Radiation Diagnostic Techniques for Dynamically Controling the Efficiency of Laser-Induced Thermotherapy for Baker’s Cyst - S. A. Chernyad’ev; V. B. Aretinskiy; N. I. Sivkova; A. V. Zhilyakov; N. Yu. Korobova; V. S. Blinov (Вестник рентгенологии и радиологии, 2019)
A popliteal cyst or Baker’s cyst is easily distinguished from other cystic or solid tumors on the magnetic resonance imaging sections. At the current level of medicine development, many options have been developed for medical and surgical treatments for popliteal cysts; however, there are still disputes on their validity and efficiency. In addition, there is no consensus on the etiology and pathogenesis of the disease. MRI is known to show similar intraarticular changes in asymptomatic patients and articular syndrome patients, which could suggest that intraarticular pathological changes played a secondary role in a number of cases of Baker’s cyst formation. Under these conditions, laser-induced thermotherapy is considered by the authors to be justified. Its main goal is to coagulate the wall of the tissue cyst, which subsequently leads to obliteration of its anastomosis and cavity. Ultrasound control is used to visualize and ensure the safety of manipulation. This paper describes a case of MRI for diagnosing a popliteal cyst and monitoring the efficiency of laser-induced thermotherapy.